META-METODE APOLOGETIKA ATAU, APOLOGETIKA (SEBAGAI) META-METODE - Kevin Juwono (Sekolah Tinggi Alkitab Tiranus, 2019)
Apologetics is often identified with public opinion as merely a matter of method, practicality and certain rational systems to answer questions about faith. The meta-method of apologetics wants to shift that opinion considering the nature of apologetics as a “space” for pneuma, which revolves through dunamis and imaginarium. Thus, apologetics is rethought as a discipline, which is open to pneumatikos dynamics, not coopted into one monocultural and instrumental rationality, and moves flexibly in the face of multicontextual reality.